Silica derived from variety of sources and its functionalized forms as an antiblock additive in polypropylene. (April 2023) - Malik, Omair; Joshi, Tina; Goel, Vishal; Kapur, Gurpreet Singh; Nebhani, Leena
Silica derived from a variety of sources and its functionalized form has been studied as an antiblock additive in polypropylene (PP). Commonly, inorganic antiblock additives are added to PP films to reduce the blocking and facilitate the separation of polymeric films. However, such types of additives can cause a reduction of clarity in transparent films. In the present work, a comparative analysis of silica obtained from various sources specifically from rice husk ash and its further functionalization/modifications using n -octyltriethoxysilane has been performed. Since silica synthesized via rice husk ash was obtained from waste (rice husk ash), this further solves the problem of ash disposal. The functionalized forms of various silica have been characterized using Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The morphological analysis was performed using scanning electron microscopy (SEM). The melt flow index (MFI), yellowness index, and other mechanical characterizations including tensile and impact strength were performed for 30–40 μm thick tubular quenched polypropylene (TQPP) films. These films were evaluated to have high transmittance (above 93%), high clarity (above 98%), and very low haze (less than 2%) indicating high transparency and improved optical properties. The blocking force and optical properties are quite similar for TQPP film containing silica synthesized from rice husk ash and commercially grade silica and hence proving silica synthesized from rice husk ash to be an effective substitute for commercial silica in TQPP films.